ANALISIS LOAN TO DEPOSIT RATIO, NON PERFORMING LOAN, NET INTEREST MARGIN TERHADAP PROFITABILITAS BANK - Nia Tresnawaty (Fakultas Ekonomi dan Bisnis Universitas Satya Negara Indonesia, 2022)
This study was conducted to examine how the variables influence Loan to Deposit Ratio (LDR), Non Performing Loan (NPL) and Net Interest Margin (NIM) on Profitability at Conventional Banks with a population of general banking sector companies listed on the Indonesia Stock Exchange for the period 2015-2019. . The method used in the study using multiple linear regression analysis, research design using causal and the type of data used is secondary data. From data processing, it can be concluded that Non Performing Loans (NPL) and Net Interest Margin (NIM) have an effect on Bank Profitability, while Loan to Deposit Ratio (LDR) has no effect on Bank Profitability. Keywords : LDR; NPL; NIM; BANK PROFITABILITY